Shade seekers & the mixer - Werbner, Richard P.; Kesupetswe, Rantii Morebodi; Gabanakgosi, Njebe Molefe (Manchester, England : International Centre for Contemporary Cultural Research, 2006)
This documentary, directed by Richard Werbner, features religious beliefs of tribal and national groups.
Previously released on DVD.
Title from resource description page (viewed Nov. 3, 2011).
Filmed in Botswana.
English.
Director, Richard Werbner.
Rantii Morebodi Kesupetswe, Njebe Molefe Gabanakgosi.
Keywords: Traditional medicine -- Botswana; Spiritual healing -- Botswana; Ancestor worship -- Botswana; Healing -- Religious aspects; Healers -- Botswana; Guérison par la foi -- Botswana; Morts -- Culte -- Botswana; Guérison -- Aspect religieux; Guérisseurs -- Botswana; Ancestor worship; Healers; Healing -- Religious aspects; Spiritual healing; Traditional medicine; Botswana; Documentary; Encoded moving images; Documentary